Structural and electrical properties of ZnO and SiO doped ZnO powder for varistor application - Mohamed, Ruziana; Osman, Nor Dalila Farhana; Yahya, Norihan; Mamat, M. H.; Malek, Mohd Firdaus; Ismail, Ahmad Syakirin; Mohd Yusoff,, Marmeezee; Khusaimi, Zuraida; Rusop, M. (AIP Publishing, 2019)
Pure zinc oxide ( ZnO ) and silica (SiO ) doped ZnO nanopowders have been prepared using solid state method. SiO were doped into ZnO at different weight percentage 1 and 3 wt.%. The structural and electrical properties of ZnO and SiO doped ZnO powder have been characterized using X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM) and electro source meter. From the results, the XRD pattern were compatible with ZnO phase structure. Based on the SEM images, the grain size of ZnO varistor is increased when doped with SiO . The obtained value of nonlinear coefficient (α) of undoped ZnO sample is low compared to SiO doped ZnO varistor . The, α value is increased as the content of SiO doped increases. The maximum value of α is at 3 wt.% of SiO doped ZnO which is 1.734 that might be can enhanced the performance of varistor . Thus, the properties of ZnO varistor can be improved when doped with SiO.